2021
DOI: 10.1103/physrevb.103.l161105
|View full text |Cite
|
Sign up to set email alerts
|

Colossal magnetoresistance via avoiding fully polarized magnetization in the ferrimagnetic insulator Mn3Si2Te6

Abstract: Colossal magnetoresistance is of great fundamental and technological significance and exists mostly in the manganites and a few other materials. Here we report colossal magnetoresistance that is starkly different from that in all other materials. The stoichiometric Mn3Si2Te6 is an insulator featuring a ferrimagnetic transition at 78 K. The resistivity drops by 7 orders of magnitude with an applied magnetic field above 9 Tesla, leading to an insulator-metal transition at up to 130 K. However, the colossal magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…A more recent example of a CMR compound is the ferrimagnetic insulator Mn 3 Si 2 Te 6 . This compound shows a CMR of ∼10 9 % if the field is applied along the magnetic hard axis, i.e., by avoiding fully spin-polarized state ( 64 ). The anisotropic CMR is predicted to be caused by the lifting of the topological nodal-line degeneracy of the spin-polarized bands depending on the spin orientation ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…A more recent example of a CMR compound is the ferrimagnetic insulator Mn 3 Si 2 Te 6 . This compound shows a CMR of ∼10 9 % if the field is applied along the magnetic hard axis, i.e., by avoiding fully spin-polarized state ( 64 ). The anisotropic CMR is predicted to be caused by the lifting of the topological nodal-line degeneracy of the spin-polarized bands depending on the spin orientation ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quite intriguingly, in the case of MST, the T C is found to increase by 11 K upon increase of pressure from 0 to 0.9 GPa. Recent rich phenomena has been demonstrated in high pressure studies on MST such as pressure-induced semiconductor to metal transition between 1.5 and 2.5 GPa and using pressure to control the apparent colossal magnetoresistance in this material. , First-principles calculations on these materials are carried out to understand the effects of pressure on the magnetic properties such as exchange coupling parameters and magnetic anisotropy energies. In CST, the exchange coupling parameters exhibit very little dependence on the pressure within the range 0–1 GPa in accord with earlier theoretical calculations .…”
Section: Discussionmentioning
confidence: 99%
“…Previous high-pressure studies ( P > 1–47 GPa) conducted on CrSiTe 3 reported structural transformations, metallization, spin reorientation transition, and a ferromagnetic to paramagnetic transition with the emergence of superconductivity. , The most recent work on CrSiTe 3 reported a dramatic increase in the T C by about 100 K with 7.8 GPa of pressure application . The sister compound, Mn 3 Si 2 Te 6 (MST), recently gained a great deal of interest due to the observance of exceptional colossal magneto resistance. Recently, MST has shown pressure-dependence of its colossal magneto resistance, along with a semiconductor to metal transition and structural phase transition …”
Section: Introductionmentioning
confidence: 99%
“…Unlike other CMR materials, the Mn 3 Si 2 Te 6 only manifests CMR when the magnetic field is applied along the magnetically hard c-axis. The in-plane resistivity of Mn 3 Si 2 Te 6 drops by seven orders of magnitude if the magnetic field is above 9 T [10,11]. It was also reported that there is an exotic quantum state driven by ab plane chiral orbital currents in Mn 3 Si 2 Te 6 [12].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Mn 3 Si 2 Te 6 , a layered ferrimagnetic nodal-line semiconductor [9,10], has attracted increasing interest since the discovery of its special angular-dependent CMR [10,11]. Unlike other CMR materials, the Mn 3 Si 2 Te 6 only manifests CMR when the magnetic field is applied along the magnetically hard c-axis.…”
Section: Introductionmentioning
confidence: 99%